2011
DOI: 10.1021/es102468z
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Mechanisms of Phenanthrene, Lindane, and Atrazine with Various Humic Acid Fractions from a Single Soil Sample

Abstract: The sorption behavior of organic compounds (phenanthrene, lindane, and atrazine) to sequentially extracted humic acids and humin from a peat soil was examined. The elemental composition, XPS and (13)C NMR data of sorbents combined with sorption isotherm data of the tested compounds show that nonspecific interactions govern sorption of phenanthrene and lindane by humic substances. Their sorption is dependent on surface and bulk alkyl carbon contents of the sorbents, rather than aromatic carbon. Sorption of atra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 37 publications
5
73
1
2
Order By: Relevance
“…The bulk elemental compositions (C, H, and N) of the biochars were determined by an element analyzer (Elementar Vario EL, Germany). Ash contents were measured by the residue weight after heating the biochars at 750°C for 6 h, and oxygen contents were calculated by mass difference (Wang et al 2011). The specific surface areas of the biochars were obtained by N 2 gas adsorption-desorption at 77 K using a surface area analyzer (Quantachrome NOVA 2200e, USA).…”
Section: Biochar and Soil Preparationmentioning
confidence: 99%
“…The bulk elemental compositions (C, H, and N) of the biochars were determined by an element analyzer (Elementar Vario EL, Germany). Ash contents were measured by the residue weight after heating the biochars at 750°C for 6 h, and oxygen contents were calculated by mass difference (Wang et al 2011). The specific surface areas of the biochars were obtained by N 2 gas adsorption-desorption at 77 K using a surface area analyzer (Quantachrome NOVA 2200e, USA).…”
Section: Biochar and Soil Preparationmentioning
confidence: 99%
“…In these components, HA/FA and humin/kerogen are two general constituents. HA/FA contains much polar organic carbon with polar functional groups, whereas humin/kerogen are enriched in condensed structures and lead to higher sorption affinity to nonpolar solutes (Kang and Xing, 2005;Luo et al, 2008;Wang et al, 2011). Meanwhile, humin/kerogen are more aliphatic and less polar than HA/FA because humin/ kerogen contains mainly aliphatic and aromatic carbon with less polar functional groups such as carboxyl (Kang and Xing, 2005).…”
Section: Model Rationalementioning
confidence: 99%
“…4), indicating that the polarity of the SOM fractions has a significant effect on the sorption capacity of atrazine. It has also been reported that higher-polarity biopolymers have a higher sorption affinity for atrazine (Shechter and Chefetz 2008), and atrazine sorption by humic substances exhibited a positive correlation with the substances' polar carbon contents (Wang et al 2011). However, this result differs from the previous reports on the sorption of apolar HOCs such as phenanthrene and lindance by fractionated SOM, which described a negative relationship between SOM polarity and logK OC (Kang and Xing 2005;Wang et al 2011).…”
Section: Effects Of Fractionated Som Properties On Atrazine Sorptionmentioning
confidence: 59%
“…One possible explanation for this discrepancy is that the sorption of atrazine, which is polar, by SOM fractions may follow a different mechanism from that of apolar HOCs due to structural and polarity differences. And also, some studies (Welhouse and Bleam 1993;Wang et al 2011) have reported that H-bouding between atrazine and the acid functionalities of HAs is a key mechanism governing atrazine sorption onto SOM, while the contribution of the π-π interaction between phenanthrene and aromatic components in humin substances (HSs) is much stronger and important than others, such as van der Waals interactions and H bonding. The rich amount of O-containing functionalities of HAs and high containing of aromatic components in humins would cause the sorption of atrazine and phenanthrene followed opposite order.…”
Section: Sorption Capability Of Som Fractions For Atrazinementioning
confidence: 99%